STRATEGIES OF CLAUSAL POSSESSION - Langacker, Ronald W. (International Journal of English Studies, 2003)
Across languages, clauses expressing possession, location, and existencc exhibit manysimilarities. To capture their evident affinity, it is often claimed that possessives derive-synclironically or diaclironically- from expressions of location/existence. This localistaccount obscures a basic contrast between two broad classes of possessive constructions, those based on HAVE-type predicates and those based on BE-type predicates. These predicates grammaticize from lexical verbs pertaining to different aspects of embodied experience, resulting in subtle semantic differences reflected in contrasting grammatical constructions for clausal possession. Moreover, both HAVE- and BE-type possessives show interesting cross-linguistic variation which should not be ignored from a typological or a cognitive linguistic perspective. Attention to these structural differences does not preclude a unified account of possessive constructions and their close relationship with locatives. These constructions all manifest our ability to mentally access one entity by invoking another as a conceptual reference point.